UNDERSTANDING GEN Z’S MENTAL HEALTH CHALLENGES - Muktifada Matilda, Arthagina; Adelia Intan Wulandari, Bernadetta Prisca; Darmanto, Darmanto (PHENOMENON : Multidisciplinary Journal Of Sciences and Research, 2025)
This study explores the psychological and emotional challenges faced by Generation Z in the digital era. The investigation focuses on four critical issues affecting their well-being: digital overload, academic and career pressure, global uncertainty, and isolation and loneliness. The increasing use of technology has led to an increase in screen time and digital engagement, resulting in cognitive fatigue and emotional exhaustion. Academic expectations and a highly competitive job market contribute to stress and burnout. Economic instability, climate change, and political unrest further intensify anxiety and uncertainty about the future. Despite being the most digitally connected generation, many Generation Z individuals experience social isolation, as online interactions often fail to provide meaningful emotional support. This study identifies key patterns and interconnections among these challenges. Findings suggest that excessive digital consumption negatively impacts mental health, while societal pressures exacerbate stress levels.